2006
DOI: 10.1097/01.ico.0000228784.46463.e9
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Trephination With the Femtosecond Laser

Abstract: This feasibility study shows that the femtosecond laser enables sufficient trephination of human donor corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
20
0
3
Order By: Relevance
“…Our findings of lower incidence of epithelial ingrowth support this hypothesis because the flap edge created by femtosecond laser has been shown to be steeply angulated, as intended, which creates a vertical and smooth edge cut 10 It has also been reported that both the macroscopic and microscopic examinations reveal smooth rectilinear cut margins with a perpendicular cut edge and almost no thermal alteration of adjacent tissue. 11 These may induce less inflammation and better adherence of flap edge to the stromal bed, acting like a seal to prevent the entry of epithelial cells underneath the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of lower incidence of epithelial ingrowth support this hypothesis because the flap edge created by femtosecond laser has been shown to be steeply angulated, as intended, which creates a vertical and smooth edge cut 10 It has also been reported that both the macroscopic and microscopic examinations reveal smooth rectilinear cut margins with a perpendicular cut edge and almost no thermal alteration of adjacent tissue. 11 These may induce less inflammation and better adherence of flap edge to the stromal bed, acting like a seal to prevent the entry of epithelial cells underneath the flap.…”
Section: Discussionmentioning
confidence: 99%
“…80 An advance in PKP has been the use of the femtosecond laser to cut both the host and donor buttons. [81][82][83][84][85] This new technique is an attempt to improve wound architecture and limit astigmatism as the wounds can be shaped (zig-zag, top-hat, or mushroom patterns), possibly allowing for closure with fewer sutures and/or tissue glue. In theory, the use of fewer sutures may limit angle distortion and lead to lower incidence of postoperative glaucoma.…”
Section: Trabeculectomymentioning
confidence: 99%
“…When using the FEMTEC femtosecond laser, a smooth stromal bed with minor remaining tissue bridges of PLDs may be visible 10 and after full-thickness trephination with this laser electron microscopy reveals more tissue bridges in thicker edematous corneas than in thinner corneas. 21 PLDs prepared by the Intralase femtosecond laser showed an excellent side-cut quality and a smooth lamellar bed. 12 However, when using a spiral laser pattern, SEM showed a stromal bed with very mild concentric circular ridges and a stucco-like texture.…”
Section: Discussionmentioning
confidence: 97%
“…However, other in vitro studies showed no thermal damage in the adjacent tissue when performing corneal trephination with the femtosecond laser. 10,21 Keratocyte activation in a LASIK flap prepared with the microkeratome or femtosecond laser and after photorefractive keratectomy has been detected. [37][38][39][40] After DLEK, activated keratocytes have been found just adjacent to the interface line.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation